DevOps Maturity Diagnosis - A Case Study in Two Public Organizations - Gimenez, Paulo J. A.; Santos, Gleison (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2020)
Organizations have been applying practices and elements of DevOps culture in the last decade to approximate development and operation teams. Many software development processes address problems associated with keeping the desired stability in organizational operations while increasingly attending the frequency and quality of software deliveries. Nevertheless, the gap between the objectives of organizational units and development and operation teams persists due to the inadequacy of the solutions adopted for the unique scenarios each organization faces. Thus, to better support creating a DevOps culture in an organization and to guide the adoption of DevOps solutions it is necessary to diagnose its maturity and their teams’ to evaluate the knowledge and skills of the people involved. We present a process to diagnose DevOps maturity. We applied it to two public organizations. We found that both organizations are evolving from level initial to level conscious. Moreover, we noticed that the participants know the DevOps culture although the organizations do not fully adopt it yet.